2009
DOI: 10.1073/pnas.0909591106
|View full text |Cite
|
Sign up to set email alerts
|

Time of feeding and the intrinsic circadian clock drive rhythms in hepatic gene expression

Abstract: In mammals, the circadian oscillator generates approximately 24-h rhythms in feeding behavior, even under constant environmental conditions. Livers of mice held under constant darkness exhibit circadian rhythm in abundance in up to 15% of expressed transcripts. Therefore, oscillations in hepatic transcripts could be driven by rhythmic food intake or sustained by the hepatic circadian oscillator, or a combination of both. To address this question, we used distinct feeding and fasting paradigms on wild-type (WT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

41
637
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 652 publications
(682 citation statements)
references
References 41 publications
41
637
1
3
Order By: Relevance
“…However, it has not escaped our attention that feeding rhythms alone can drive rhythmic gene transcription under constant darkness even in the complete absence of a functional clock. 5 In addition, only a small number of rhythmic transcripts in the liver are direct targets of clock regulators. 9 In fact, our results showed that several metabolic tissues such as skeletal muscle, heart, and kidney lack robust BAF60a rhythmicity, whereas they have nice oscillations of clock components.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has not escaped our attention that feeding rhythms alone can drive rhythmic gene transcription under constant darkness even in the complete absence of a functional clock. 5 In addition, only a small number of rhythmic transcripts in the liver are direct targets of clock regulators. 9 In fact, our results showed that several metabolic tissues such as skeletal muscle, heart, and kidney lack robust BAF60a rhythmicity, whereas they have nice oscillations of clock components.…”
Section: Discussionmentioning
confidence: 99%
“…5,9 Given that BAF60a is ubiquitously expressed, the specificity of BAF60a regulation should be achieved by simultaneously orchestrating BAF60a and other tissue-specific transcriptional factors, whose circadian expression is restricted to a subset of peripheral organs/tissues. One good example is the nuclear receptor PPARa, which is a clock-controlled metabolic sensor mostly expressed in the liver, where it regulates fatty acid boxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 368 circadian clock-driven transcripts were identified under fasting conditions in WT mice. When WT mice were restricted to daytime feeding, 4960 transcripts displayed rhythmic expression (Vollmers et al, 2009), showing that there is a clear synergy between the circadian and metabolic systems in the regulation of rhythmic transcription in the liver. These studies also suggest that there is an independent but interactive organization that links metabolic controls with circadian clocks.…”
Section: The Circadian Systemmentioning
confidence: 99%
“…The latter phenomenon can be achieved by the rhythmic expression of enzymes involved in the anabolic or catabolic reactions. A recent study revealed that up to 15% of the liver transcriptome is expressed in a rhythmic fashion (Vollmers et al, 2009) and food availability directly drives the expression of many of these genes. However, a relatively small subset of these transcripts remained rhythmic even under fasting conditions, i.e.…”
Section: Introductionmentioning
confidence: 99%